Optimizing glycine concentration to enhance gibbsite-catalyzed abiotic humification of catechol and glucose - Kai Li; Qi Han; Jingjing Wang; Donghui Dai; Haoyu Gao; Jingwei Gao; Mingshuo Wang; Haihang Sun; Shuai Wang (PLoS ONE, 2025)
The Maillard reaction represents a pivotal biochemical pathway for the abiotic formation of humic-like substances (HLSs); however, the regulatory role of gibbsite ( α -Al(OH) 3 ) in mediating this process remains insufficiently explored. This study systematically evaluated the effects of glycine concentration (0–0.24 mol/L) on the abiotic humification of catechol (0.06 mol/L) and glucose (0.06 mol/L) in the presence of gibbsite, using a sterile liquid shake-flask incubation system. The molecular complexity of the supernatant, total organic carbon (TOC) retention efficiency, and structural evolution of HLSs isolated from the dark-brown residue were analyzed through UV-Vis spectroscopy, TOC quantification, Fourier-transform infrared (FTIR) spectroscopy, and elemental analysis. Results demonstrated that: (1) The Gly0.24 treatment (0.24 mol/L glycine) achieved the minimal TOC loss, with a reduction of only 26.0% compared to 49.8% in the control group (without glycine). This carbon-preserving effect was attributed to the formation of Al–C complexes. (2) At a glycine concentration of 0.12 mol/L, the resulting HLSs exhibited the highest degree of aromatic condensation—evidenced by the lowest E 4 /E 6 ratio (2.11)—and the richest content of oxygen–containing functional groups (O/C atomic ratio = 1.38). Concurrently, FTIR analysis indicated suppressed vibration of Al–O bonds in this treatment, suggesting that moderate glycine concentrations could modulate gibbsite–organic interactions to favor humification. (3) The Gly0 (no glycine) and Gly0.06 (0.06 mol/L glycine) treatments yielded the maximum humic-like acid (HLA) content, with respective increases of 1295.9% and 1034.6% relative to the control. This observation implies that low glycine levels (or its absence) primarily promoted the polymerization of catechol and glucose into HLA, rather than diverting carbon toward other reaction products. (4) Higher glycine concentrations (0.12–0.24 mol/L) significantly enhanced the accumulation of nitrogen-containing compounds in HLA, leading to a marked decrease in the C/N ratio (down to 8.7 in Gly0.24). This trend confirmed that excess glycine served as a nitrogen donor, facilitating the incorporation of nitrogen moieties into HLA structures during humification. These findings highlighted that 0.12 mol/L glycine represented the optimal concentration for optimizing abiotic humification in the gibbsite system, as it balances two critical processes: aromatic polycondensation (a hallmark of humification degree) and the enrichment of oxygen-containing functional groups (key for HLS reactivity). This study provided novel mechanistic insights into gibbsite-catalyzed Maillard pathways, thereby advancing the development of strategies for efficient carbon sequestration in terrestrial ecosystems and the valorization of lignin-rich agricultural/industrial wastes into high-value humic-based products.